2020
DOI: 10.1111/jcpt.13161
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drug‐related problems and associated factors in ambulatory patients in China

Abstract: Summary What is known and objective This study aimed to investigate the prevalence and the type of drug‐related problems (DRPs) in ambulatory patients and identify factors that may be associated with risk of DRPs. Methods Consecutive patients were enrolled from pharmacist outpatient clinics between January 2018 and June 2019. The pharmacists performed a comprehensive assessment of the patient's drug therapy. The DRPs and recommendations were evaluated using the DOCUMENT classification system. Results and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Participants in the two latter studies had a higher number of medications and comorbidities than participants in the present study. Previous studies have indicated these factors increased the number of DRPs [6][7][8]30]. In this study, polypharmacy and multiple comorbidities were related to DRPs, consistent with previous research.…”
Section: Discussionsupporting
confidence: 91%
“…Participants in the two latter studies had a higher number of medications and comorbidities than participants in the present study. Previous studies have indicated these factors increased the number of DRPs [6][7][8]30]. In this study, polypharmacy and multiple comorbidities were related to DRPs, consistent with previous research.…”
Section: Discussionsupporting
confidence: 91%
“…The prevention, identification and solution of DRPs constitutes the core of pharmaceutical care in which clinical pharmacists, together with the multi-disciplinary team (MDT), make an effort to improve therapeutic outcomes and the quality of life in patients [ 7 9 ]. Clinical pharmacists are involved in the entire treatment process from the beginning of patient hospitalization including medication reconciliation, participating in clinical ward rounds, providing medication consultation and so on.…”
Section: Introductionmentioning
confidence: 99%
“…When the death rates were evaluated in terms of gender, the rate was higher in men than in women. 18 More specifically, in studies related to DRPs, problems in ambulatory patients, 19 neurological problems, 20 respiratory problems, and cardiac problems have been reported. 21,22 A drug-related problem (DRP) is defined as an event or circumstance involving drug therapy that actually or potentially interferes with desired health outcomes.…”
Section: Introductionmentioning
confidence: 99%